1973
DOI: 10.2307/2272055
|View full text |Cite
|
Sign up to set email alerts
|

Borel sets and Ramsey's theorem

Abstract: Definition 1. For a set S and a cardinal κ,In particular, 2ω denotes the power set of the natural numbers and not the cardinal 2ℵ0. We regard 2ω as a topological space with the usual product topology.Definition 2. A set S ⊆ 2ω is Ramsey if there is an M ∈ [ω]ω such that either [M]ω ⊆ S or else [M]ω ⊆ 2ω − S.Erdös and Rado [3, Example 1, p. 434] showed that not every S ⊆ 2ω is Ramsey. In view of the nonconstructive character of the counterexample, one might expect (as Dana Scott has suggested) that all sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
142
0
8

Year Published

1976
1976
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(150 citation statements)
references
References 6 publications
(2 reference statements)
0
142
0
8
Order By: Relevance
“…This last inclusion is true since if q E C and $ is a monotone enumeration of q, then $ = kj for j < J. Hence, (A is the set of those p such that zJco a&, is a Cauchy sequence if kj is a monotone enumeration of p.) By a theorem of F. Galvin and K. Prikry [3] there is q E P(w) such that either (I) for every I r q, t E P(u) -f E A, or (II) for every t C q, r E P(w) =+ I E B. For the sequence {ej)iSs either (b) holds (in case (II)) or in case (I) we shall indicate how to pick a subsequence of it for which (a) holds.…”
mentioning
confidence: 93%
“…This last inclusion is true since if q E C and $ is a monotone enumeration of q, then $ = kj for j < J. Hence, (A is the set of those p such that zJco a&, is a Cauchy sequence if kj is a monotone enumeration of p.) By a theorem of F. Galvin and K. Prikry [3] there is q E P(w) such that either (I) for every I r q, t E P(u) -f E A, or (II) for every t C q, r E P(w) =+ I E B. For the sequence {ej)iSs either (b) holds (in case (II)) or in case (I) we shall indicate how to pick a subsequence of it for which (a) holds.…”
mentioning
confidence: 93%
“…The notion has been formally defined by Darji [40], though it was already studied by Galvin and Prikry in [55]. Instead of using the original definition for this class, we will use its characterization due to Nowik [97] in which we consider P(ω) as a Polish space by identifying it with 2 ω via the characteristic function.…”
Section: Uniformly Completely Ramsey Null Setsmentioning
confidence: 99%
“…If P is a partition and X is an infinite subset of ω, then X lands in P if every infinite subset of X is in P, and X avoids P if no infinite subset of X is in P. A partition P is Ramsey if there is an infinite set X that either lands in P or avoids P. The theorems we are interested in are of the form "every well-behaved partition is Ramsey." A number of authors have shown independently that if P is open in the usual topology then it is Ramsey (see [4]), and the conclusion has been extended to Borel sets by Galvin and Prikry [4] and analytic sets by Silver [8,2].…”
Section: Introductionmentioning
confidence: 99%